2021
DOI: 10.1007/s10620-021-07040-z
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Disease and COVID-19 Vaccination: A Patients’ Survey

Abstract: Background Vaccination against COVID-19 is a major public health challenge, including the community of patients with inflammatory bowel disease. Vaccination coverage is suboptimal in inflammatory bowel disease population. It is of paramount importance to ensure an effective and rapid vaccination program with the adherence of the largest number of well-informed patients. Aims We assessed the acceptance of COVID-19 vaccination among inflammatory bowel disease patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 17 publications
2
17
0
Order By: Relevance
“…It is not known whether health care professionals received recommendations regarding COVID-19 vaccination. In our study, half of patients with IBD wished to be vaccinated against SARS-CoV-2, and this rate was similar to that reported in the French general population [1]. In Italy, a survey measured the acceptance of anti-SARS-CoV-2 vaccination in an IBD population, and the proportion of patients willing to be vaccinated against SARS-CoV-2 was 53.6%, which is similar to our cohort [2].…”
Section: Replysupporting
confidence: 88%
See 1 more Smart Citation
“…It is not known whether health care professionals received recommendations regarding COVID-19 vaccination. In our study, half of patients with IBD wished to be vaccinated against SARS-CoV-2, and this rate was similar to that reported in the French general population [1]. In Italy, a survey measured the acceptance of anti-SARS-CoV-2 vaccination in an IBD population, and the proportion of patients willing to be vaccinated against SARS-CoV-2 was 53.6%, which is similar to our cohort [2].…”
Section: Replysupporting
confidence: 88%
“…We read with interest the article by Bénédicte Caron et al, who performed a survey to assess the acceptance of COVID-19 vaccination among patients with inflammatory bowel disease (IBD) [1]. They found that half of the patients with IBD wished to be vaccinated against SARS-CoV-2.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Our findings suggest that the proportion of patients with IBD who are hesitant about vaccination against COVID-19 vaccine is similar to that of the general population, as reported in different Japanese studies [6][7][8]. This prevalence of vaccine hesitancy in this study was relatively low compared with that in previous reports of patients with IBD [40,42]. This could be due to the timing of the study because COVID-19 has become recognized as a long-term issue and the high effectiveness and safety of vaccination have been widely recognized, although intentions vary widely according to the characteristics of the patient sample, country, and time period [6,[48][49][50].…”
Section: Hesitancy and Acceptance Of Ocivd-19 In Patients With Ibdsupporting
confidence: 82%
“…In a recent French study, 104 IBD patients were asked to answer a questionnaire. In total, 54.8% of them expressed the intention to receive anti-COVID-19 vaccination as soon as possible, and this percentage was comparable to that of the general population in France [112].…”
Section: Vaccines Against Covid-19 and Inflammatory Bowel Diseases: A New Challengementioning
confidence: 74%